Hubungan Nomophobia Dengan Kualitas Tidur Pada Mahasiswa S1 Keperawatan Institut Kesehatan Payung Negeri Pekanbaru - Dian Agusti Varesya; Desti Puswati; Fitri Dyna; Cindy Febriyeni (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Nomophobia (no mobile phone phobia) is a condition of anxiety experienced by individuals when they are unable to access or use their smartphones. Among university students, excessive smartphone use can lead to various negative impacts, one of which is poor sleep quality. Inadequate sleep quality affects physical health, mental health, concentration ability, and academic performance. This condition is a particular concern for nursing students who face high academic demands and clinical practice responsibilities. This study aimed to determine the relationship between the level of nomophobia and sleep quality among undergraduate nursing students at the Institute of Health Payung Negeri Pekanbaru. A quantitative method with a correlational design and a cross-sectional approach was used. The study population consisted of 274 first-year undergraduate nursing students, with a sample of 163 respondents selected using stratified random sampling. The research instruments included the Nomophobia Questionnaire based on the study by Puswati and Sari (2021), which refers to the Nomophobia Questionnaire (NMP-Q), and a sleep quality questionnaire based on the study by Juliana (2024), adapted from the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using a bivariate Chi-Square test to examine the relationship between nomophobia and sleep quality. The results showed that 74.2% of respondents experienced moderate levels of nomophobia, and 91.4% had poor sleep quality. The Chi-Square test revealed a p-value of 0.000 (p < 0.05), indicating a significant relationship between nomophobia and sleep quality among undergraduate nursing students at the Institute of Health Payung Negeri Pekanbaru. This study is expected to serve as a reference for educational institutions and students in providing education on healthy smartphone use, the dangers of nomophobia, and the importance of maintaining good sleep quality through seminars or mental health–related courses.